HUBUNGAN PERNIKAHAN USIA DINI DENGAN KEJADIAN STUNTING PADA BALITA USIA 0-59 BULAN DI DESA BONDE UTARA - nurul ainun safitri (Jurnal Kesehatan Marendeng, 2023)
Stunting is a condition where a toddler’s body does not reach the appropriate length or height based on age standards. This research aims to determine the relationship between early marriage and the incidence of stunting in north bonde village. The research method used is analytical observational research with a cross sectional approach. The population in this study was 107 toddlers aged 0-59 months in February 2023. The sampling with technique used purposive sampling with certain criteria so that 60 repondents were obtained. Data collection uses a checklist sheet. The research location is in north bonde village. The time of the research was from august to September 2023. The results of the research were mostly early marriages of 51,7%, stunting of 50,0% and chi-square test analysis data (p=0,605). The conclusion was there was no relationship between early marriages and the incidence. Conclusion there is no significant relationship between early marriage and the incidence of stunting in toddlers aged 0-59 months in north bonde village